(untitled) (Experimental biology, 2016)
The authors of the article give a complete geobotanical characterization and floristic analysis Taraxacum kok-saghyz communities in conditions of mountainous valley Tekes river. They note that Taraxacum kok-saghyz is really rare plant with a limited distribution area. Taraxacum kok-saghyz population in a mountainous valley Tekes is not in danger. Natural regeneration of Taraxacum kok-saghyz is quite normal. The only causes of concern is digging roots of Taraxacum kok-saghyz for raw materials. Under natural conditions, should not be allowed it harvesting for raw materials. Because we can easily lose population of this valuable technical and endemic plant species. Harvesting the roots of Taraxacum kok-saghyz for raw materials can be only in artificial plantations.